Annual Plan 1993-94 Scheme-Wise Proposals Union Territory of Pondicherry - Planning Commission (Planning Commission, 1993)
Pondicherry Panchayats Act of 1973 and Municipalities Act of 1973 came into force in 1974. There are 4 Municipalities, namely, Pondicherry, Karaikal, Mahe and Yanam. There are 11 commune panchayats - 6 in Pondicherry region, namely, Ozukarai, Villianur, Mannadipet, Ariankuppam, Bahour, Nettapakkam and 5 in Karaikal region, namely, Thirunallar, Naravy, Nedungadu, Kottucherry and T. R.Pattinam.
Union Territory of Pondicherry